Functional Transformations in Criminal Law and Their Impact on Criminalizing Institutional Discrimination - Abbood, Sarmad; Abdullah, Firas (Journal of Legal Sciences, 2026)
Functional transformations in the roles and tasks of criminal law and contemporary social and historical developments reflect the urgent need to comprehensively comprehend some of the new crimes with the aim of including them within criminal legislation and determining appropriate penalties for them. Among these new crimes, the crime of institutional discrimination stands out as a form of general discrimination that occurs within the legal institutions themselves. It is usually based on unjustified discrimination between individuals based on legally protected characteristics such as race, gender, religion, or nationality. These actions negatively affect rights and disrupt the course of justice, which makes it necessary to strengthen the legal system’s ability to deal with them effectively by modernizing the roles of criminal law and amending legislation. Criminal, reflecting societal and legal developments. The development of criminal law reflects the comprehensive development in its multiple functions with its transition from traditional roles to contemporary roles that include the educational function by enhancing legal awareness and educating the public about legal rights and duties, or the moral function includes promoting criminal law values ​​and morals in society and combating immoral or immoral behaviors. The forward-looking function includes when criminal law attempts to adapt to future developments and confront potential criminal challenges, or its symbolic function, given that criminal law represents a symbol of justice and order in society, which contributes to building trust between citizens and the legal system.